A Review on Refusals in Second Language Pragmatics Instruction - Huan Zhu (Journal of Linguistics and Communication Studies, 2023)
Research on the development of L2 pragmatic competence has focused chiefly on speech acts. However, this does not mean that speech acts are sufficiently understood. Refusals have been much less studied than requests, though they are the second most investigated speech act (Ren, 2022). This paper aims to make contributions to L2 refusal instruction by reviewing previous studies on L2 refusals. In conclusion, research on L2 refusal instruction has mostly concentrated on implicit and explicit instruction, ignoring the role of task-based instruction and other instructions. However, they are widely used in other second-language acquisition (SLA) areas, like morphosyntax. Individual learner factors like L2 proficiency and working memory are investigated in L2 refusal instruction. This paper aims to make contributions to L2 pragmatics by reviewing empirical research on L2 refusals.